2020
DOI: 10.11606/s1518-8787.2020054002207
|View full text |Cite
|
Sign up to set email alerts
|

Infecções sexualmente transmissíveis em mulheres privadas de liberdade em Roraima

Abstract: OBJETIVO: Avaliar a prevalência de infecção por vírus da imunodeficiência humana (HIV), sífilis e hepatite B entre mulheres privadas de liberdade do estado de Roraima e sua correlação com percepções, conhecimento e fatores comportamentais. MÉTODO: Trata-se de estudo de corte transversal, com amostragem sistemática simples, realizado na Cadeia Pública Feminina de Boa Vista, estado de Roraima, no ano de 2017. Foram avaliadas 168 detentas (93,8% da população) por meio de entrevista face a face e testes rápidos. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 12 publications
1
19
1
6
Order By: Relevance
“…In our analysis of 32 publications, 23 papers evaluate the prisoners' educational levels 3,14–19,21–27,30,34,35,39,40,42–44,50 . Most papers had reported that the majority of their participants in the survey/research had low levels of education in comparison to the general population, and mostly only had completed some years of primary/elementary education.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis of 32 publications, 23 papers evaluate the prisoners' educational levels 3,14–19,21–27,30,34,35,39,40,42–44,50 . Most papers had reported that the majority of their participants in the survey/research had low levels of education in comparison to the general population, and mostly only had completed some years of primary/elementary education.…”
Section: Discussionmentioning
confidence: 99%
“…Item 32, which started with an even lower mean in the pre-test (0.53) and deals with imprisoned women’s vulnerability to STIs when compared to free women, was a subject matter of great controversy. Despite the game portraying this idea, based on scientific studies [ 4 , 43 , 44 ], it was common for imprisoned women to disagree with this information. This is because the unit provides access to a series of preventive services that, under conditions of freedom, they would have difficulty enjoying, taking into account the social vulnerability of the environment where they were previously inserted.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the lack of knowledge on the subject, distorted perceptions and risky behaviors adopted during incarceration. [ 4 ]. Thus, the female population tends to need more health care, mainly with regard to STI prevention, which is emphasized by the National Plan for Health in the Penitentiary System ( Plano Nacional de Saúde no Sistema Penitenciário , PNSSP), which provides for health education, STI diagnosis, control and treatment actions; distribution of condoms; and elaboration of instructional educational material [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao intuito do estudo, a temática mais utilizada sobre IST dentro dos presídios femininos foi o HIV. Tais informações corroboram os dados do rela- Educação em saúde acerca das infecções sexualmente transmissíveis no ambiente prisional feminino: revisão integrativa tório do Departamento Nacional Penitenciário de Mulheres de que sífilis e HIV são as IST que mais acometem a população feminina do sistema carcerário nacional 22 . Quando são trazidos à tona a realidade de mulheres usuárias de drogas, em geral, têm maior probabilidade de ter parceiros que também são usuários de drogas e, com menos recursos econômicos para comprar drogas, têm maior probabilidade de se envolver em intercâmbio sexual para obter essas substâncias 16 .…”
Section: Discussionunclassified